Perlindungan Hukum Terhadap Pejabat Pembuat Akta Tanah (PPAT) dalam Peralihan Hak Atas Tanah Kavling Perumahan yang Menjadi Objek Sengketa - Eva Husnun Nabila Octavyani (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the legal protection of Land Deed Officials (PPAT) in the transfer of rights over residential land parcels that become objects of disputes. Residential land parcels are often involved in disputes that include claims from parties who feel aggrieved, even though the transfer of rights has been carried out legally by PPAT. In this research, the author explores the role of PPAT, the factors causing disputes, and the legal protection for PPAT in cases of land disputes. The methodology used is a normative juridical approach with descriptive analysis of the applicable laws and regulations, as well as a case study of land disputes involving PPAT. The findings of this study highlight the importance of clear legal protection for PPAT in dealing with land disputes, even though they have followed the procedures as prescribed by the law.